2013
DOI: 10.1128/jvi.00262-13
|View full text |Cite
|
Sign up to set email alerts
|

Substitutions T200A and E227A in the Hemagglutinin of Pandemic 2009 Influenza A Virus Increase Lethality but Decrease Transmission

Abstract: Modifications in the hemagglutinin (HA) glycoprotein of the influenza A virus are believed to be a catalyst for previous world pandemics (1, 2). This includes reassortment between cocirculating animal and human viruses and mutations in the HA which grant better transmissibility between hosts (3). The pandemic influenza A virus from 2009, A(H1N1)pdm09, originated from reassortment among three cocirculating swine and avian-like viruses; hence, its HA comes from a swine virus origin (4). Although little is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Modeling of the mutations in a structure model of pH1N1 HA showed that changes in receptor binding are likely explained by the effect of these mutations on hydrogen bond formation either with the 190 helix or with the sialylated glycan directly. Importantly, mutations in HA that affected receptor binding, as detected with the recombinant protein approach, were also shown to affect receptor binding in the context of complete virus particles (13,16; this study). Several of the substitutions that affected receptor binding in vitro were shown by others to affect the , and blue (GlcNAc).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Modeling of the mutations in a structure model of pH1N1 HA showed that changes in receptor binding are likely explained by the effect of these mutations on hydrogen bond formation either with the 190 helix or with the sialylated glycan directly. Importantly, mutations in HA that affected receptor binding, as detected with the recombinant protein approach, were also shown to affect receptor binding in the context of complete virus particles (13,16; this study). Several of the substitutions that affected receptor binding in vitro were shown by others to affect the , and blue (GlcNAc).…”
Section: Discussionmentioning
confidence: 57%
“…Remarkably, formation of this new bond decreases binding avidity, whereas the disruption of the water-supported network by S186P increases binding. pathogenicity or transmission of pH1N1 viruses in animal models (16,31), demonstrating that changes in receptor binding identified with our recombinant protein approach are of biological significance in vivo, but the specific impact on viral phenotypes of the HA substitutions studied here, with the exception of A200T, remains to be determined.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…All animal experiments were conducted by using protocols approved by the Icahn School of Medicine at Mount Sinai Institutional Animal Care and Use Committee (IACUC). Ferrets were provided access to food and water ad libitum (9,10,22,23).…”
mentioning
confidence: 99%